Increasing Energy Conservation Behavior of Individuals towards Sustainable and Energy-Efficient Communities - Ceylan, Rumeysa; Ozbakir, Aysegul (MDPI, 2022)
The energy crisis is the foremost concern for the developing world, predominantly in European countries. The global energy demand will increase significantly by 2050, while natural resources dramatically decrease every day. However, net-zero emissions targets, climate emergency calls (1.5 degrees C global warming limit), smart environmental transformations, and energy transition efforts bring hope for fundamental changes in climate action globally. One of the best and most cost-effective strategies to achieve reduced energy consumption is encouraging energy conservation actions, which should begin at the household level and further spread to the community level. Therefore, this study aims to point out the critical role and growing importance of the 'human' dimension of smart cities via a behavior-based approach. The main purpose of the study is to measure the effect of feedback and intervention mechanisms on the energy conservation behavior of 100 volunteers who live in Kadikoy, Istanbul, over eight months through a behavioral questionnaire. The findings indicate that the feedback and intervention mechanisms affect volunteers' energy conservation behaviors in the following behavioral groups: intention (t(99) = -2.75, p = 0.00), attitude (behavioral beliefs and outcome evaluations) (t(99) = 2.29, p = 0.02), subjective norms (t(99) = -4.07, p = 0.00), and perceived behavioral control (control beliefs and influence behavior) (t(99) = 3.60, p = 0.00). Moreover, among the four variable groups, participants' intention, subjective norms, and perceived behavioral control scores are relatively high in favor of actual energy conservation behavior. Hence, the findings of the study will provide valuable insights for the local government in terms of empowering citizen participation and data-driven feedback loops, from the bottom-up energy transition perspective, via smart technologies in smart cities.
Keywords: energy conservation behavior; sustainable energy transition; energy-saving behavior; smart community; climate change; PLANNED BEHAVIOR; CONSUMPTION BEHAVIOR; FEEDBACK; POWER; MODEL; Engineering; Urban Studies